Shear Stress Modulates Resistin‐Induced CC Chemokine Ligand 19 Expression in Human Aortic Endothelial Cells. Issue 9 (26th May 2015) - Yu, Hong‐Ren; Sung, Mao‐Ling; Kuo, Hsing‐Chun; Lin, Chi‐Hui; Chen, Cheng‐Nan
Abstract : Resistin may be an important link between obesity and diabetes. Recent studies have suggested an association between resistin and atherogenic processes. In addition, CCL19 is highly expressed in human atherosclerotic lesions. The interplays among resistin, CCL19, and shear stress in regulating vascular endothelial function are not clearly understood. In the present study, resistin stimulation induced dose‐ and time‐dependent CCL19 expression in human aortic endothelial cells (HAECs). By using neutralizing antibody and small interfering (si)RNA, we demonstrated that toll‐like receptor 4 (TLR4) is critical for resistin‐induced CCL19 expression. Transcription factor ELISA and chromatin immunoprecipitation assays showed that resistin increased NF‐κB‐DNA binding activities in ECs. Inhibition of NF‐κB activation by specific siRNA blocked the resistin‐induced CCL19 promoter activity and expression. Preshearing of ECs for 12 h at 20 dyn/cm 2 inhibited the resistin‐induced NF‐κB activation and CCL19 expression. Our findings serve to elucidate the molecular mechanisms underlying the resistin induction of CCL19 expression in ECs and the shear‐stress protection against this induction. J. Cell. Physiol. 230: 2120–2127, 2015. © 2015 Wiley Periodicals, Inc.